Enhancing Motivation Of Students Completion Of Study Using Rebt Counseling Based On Islam - Eka Damayanti; Muchlisah Muchlisah; Muthmainnah Muthmainnah; Subhan Ajrin Sudirman; Muhammad Rusydi Rasyid; Wahyuni Ismail (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2021)
Higher education institutions are expected to produce high-quality graduates on time though with specialized knowledge in their fields. However, the reality is that several learners are unable to complete their education during this normal period of time. Many factors and challenges are encountered, such as students' emotional state, social environment, physical health, and so forth. The purpose of this study is to describe an increase in motivation for study completion after Rational Emotive Behavior Therapy (REBT) counseling for Biology Education students who are on the verge of dropping out. This descriptive quantitative analysis was conducted out towards the Department of Biology Education, Faculty of Tarbiyah and Teacher Training, Alauddin State Islamic University, Makassar. Purposive criteria were used to select as many as seven research participants who were on the verge of dropping out of the study. The data collection instruments used were a motivation scale, a motivation screening sheet, an ABCDEF model REBT therapy worksheet, an Islamic-based REBT module, and documentary evidence. The data analysis method used is descriptive statistics, and indeed the findings demonstrate an increase in the average value of motivation for completion of the study before (60.14) and after treatment (63.14). Meanwhile, the screening data showed that each subject experienced an increase in motivation to complete the study at each counseling session. The study participants also recognized the value of the Islamic-based REBT method in increasing motivation to complete their studies.